1981
DOI: 10.1002/hlca.19810640321
|View full text |Cite
|
Sign up to set email alerts
|

Studies of molecular ions. IX. Detection of low‐lying ‘non‐Koopmans’ states in polyacetylene molecular cations

Abstract: Comparison of the photoelectron spectra of the title compounds with the electronic absorption spectra of the corresponding radical cations led to the detection of low lying ‘Non‐Koopmans’‐states in the ionic species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A comparison between the PE spectra of dimethyl- and disilylacetylene reveals a higher (10.46 eV) ionization energy for the silyl substituted compound than for dimethylacetylene (9.61 eV) as expected for the less electron donor properties of the SiH 3 group compared with the CH 3 group. The photoelectron spectra of bis(trimethylsilyl)di- and triacetylene show a shift of the π-bands toward lower energy when compared to the t -butyl substituted congeners . The results when acetylene and 1,3-butadiyne were substituted with (H 3 C) 3 Ge , and (H 3 C) 3 Sn were similar.…”
Section: Quantum Chemical Calculations and Spectroscopic Investigatio...mentioning
confidence: 87%
“…A comparison between the PE spectra of dimethyl- and disilylacetylene reveals a higher (10.46 eV) ionization energy for the silyl substituted compound than for dimethylacetylene (9.61 eV) as expected for the less electron donor properties of the SiH 3 group compared with the CH 3 group. The photoelectron spectra of bis(trimethylsilyl)di- and triacetylene show a shift of the π-bands toward lower energy when compared to the t -butyl substituted congeners . The results when acetylene and 1,3-butadiyne were substituted with (H 3 C) 3 Ge , and (H 3 C) 3 Sn were similar.…”
Section: Quantum Chemical Calculations and Spectroscopic Investigatio...mentioning
confidence: 87%
“…However, optical transitions involving electron promotion to virtual orbitals, (B-and C-type transitions in Scheme 1), which bear no direct relation to Koopmans' theorem, are also observed in radical ion spectra. [11][12][13] On the basis of the above concepts, we concluded some time ago that the energies E i of A-type transitions in a radical cation (where the nth MO is singly occupied) should correspond to differences of orbital energies ∆ i ) n -(n-i) calculated for the corresponding neutral, closed-shell compound containing 2n electrons. Furthermore, we demonstrated that optical transition energies of radical cations can be successfully predicted using this approach based on Koopmans' theorem, even for systems that undergo large geometry changes upon ionization, by carrying out the calculations at the optimized geometries of the radical cations (we termed these "neutral at cation geometry" or NCG calculations).…”
Section: Introductionmentioning
confidence: 97%
“…However, optical transitions involving electron promotion to virtual orbitals, (B-and C-type transitions in Scheme 1), which bear no direct relation to Koopmans' theorem, are also observed in radical ion spectra. [11][12][13] http://doc.rero.ch…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation